2015
DOI: 10.4103/0971-6203.170796
|View full text |Cite
|
Sign up to set email alerts
|

Setup error analysis in helical tomotherapy based image-guided radiation therapy treatments

Abstract: The adequacy of setup margins for various sites in patients treated with helical tomotherapy was investigated. A total of 102 patients were investigated. The breakdown of the patients were as follows: Twenty-five patients each in brain, head and neck (H and N), and pelvis, while 12 patients in lung and 15 in craniospinal irradiation (CSI). Patients were immobilized on the institutional protocol. Altogether 2686 megavoltage computed tomography images were analyzed with 672, 747, 622, 333, and 312 fractions, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…demonstrated that with a margin of 10 mm applied in both vertical and longitudinal direction, and a margin of 7 mm along the lateral direction has adequate target volume coverage in pelvic malignancies in the supine position. [6] Patni et al . also demonstrated a CTV-PTV margins expansion of 0.584, 1.036, and 0.566 cm in AP, SI, and ML directions, respectively, in pelvic malignancies in supine position.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…demonstrated that with a margin of 10 mm applied in both vertical and longitudinal direction, and a margin of 7 mm along the lateral direction has adequate target volume coverage in pelvic malignancies in the supine position. [6] Patni et al . also demonstrated a CTV-PTV margins expansion of 0.584, 1.036, and 0.566 cm in AP, SI, and ML directions, respectively, in pelvic malignancies in supine position.…”
Section: Discussionmentioning
confidence: 99%
“…have published and validated previously PTV margins specifically to their center for pelvis in the supine position. [67] In our radiotherapy center, 3DCRT and IMRT with image guidance is a routine practice. This study was conducted to assess the setup errors for rectal cancer patients being treated with 3DCRT in prone position, to determine the optimal CTV-PTV margin specific to our center.…”
Section: Introductionmentioning
confidence: 99%
“…CHB was diagnosed following the 2015 guidelines for prevention and treatment of CHB. [ 11 ] Patients with acquired immunodeficiency syndrome, history of chemotherapy, or other chronic immune disorders were excluded. Written informed consent was obtained from all patients.…”
Section: Methodsmentioning
confidence: 99%
“…in the latest issue of your journal. [ 1 ] The current rapid introduction of pretreatment (tomotherapy megavoltage computed tomography (CT) and cone-beam CT on Varian and Elekta linacs) and in-treatment (CyberKnife, ViewRay) image guidance (IG) needs a careful assessment of these technologies in order to establish their optimal usage. The authors investigated the position correction shifts for 102 patients treated with helical tomotherapy using megavoltage CT for matching the patient position of the day to the planning CT study.…”
mentioning
confidence: 99%
“…The margins calculated by Thondykandy et al . [ 1 ] correspond only to a part of the total planning target volume (PTV) construction accounting for interfraction motion as explained in BIR publication. [ 3 ] These margin values can be used to account for positioning errors if no pretreatment IG is performed.…”
mentioning
confidence: 99%